2021
DOI: 10.1093/jphsr/rmab009
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the willingness of community pharmacists to test–treat–immunize during the COVID-19 pandemic in Puerto Rico

Abstract: Objective The objective of this study was to assess community pharmacists’ willingness to test, treat and immunize for COVID-19 in Puerto Rico. Methods In this cross-sectional study, a 37-item survey was distributed via email and social media in May 2020 through REDCap online software. All licensed community pharmacists in Puerto Rico (N = 1200) were invited to complete the survey. Retired community pharmacists were excluded.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The survey findings have been published elsewhere. 19 For this article, only the open-ended questions were analyzed and reported.…”
Section: Methodsmentioning
confidence: 99%
“…The survey findings have been published elsewhere. 19 For this article, only the open-ended questions were analyzed and reported.…”
Section: Methodsmentioning
confidence: 99%
“…The vaccine application and testing by community pharmacists showed divergence in acceptance for the service. In addition to easy accessibility of these services to the population, some authors reported the willingness of professionals to test and immunize, contributing to the information, advertising, and promotion of vaccines, 26 , 27 , 29 , 30 while others showed dissatisfaction with this aspect, due to overload, lack of support, training, or confidence in the vaccine. 28 …”
Section: Main Strategies For Addressing Covid-19mentioning
confidence: 99%
“…43 Another survey in Puerto Rico reported that more than 75% of community pharmacists were willing to treat and to administer vaccines to patients; working in community pharmacy and educational status of PharmD degree or higher were factors linked with increased willingness to immunize. 44 Based on operational models for pandemic vaccinations at regional supermarket chain pharmacies, it has been suggested that health authorities can provide epidemiologic data to pharmacies to scale a projected pandemic response. Hub pharmacies at the center of regions with the ability to accommodate large patient volumes, pharmacies located at major roads or intersections, and those with large parking areas can be ideal as vaccination centers for in-store or drivethrough vaccination; the presence of multiple stations for preand postvaccination waiting will be a further advantage.…”
Section: Triage Risk Assessment Reporting and Referral Of Covid-19 Casesmentioning
confidence: 99%